Adolescent alcohol use: Social comparison orientation moderates the impact of friend and sibling behaviour. (20th September 2014) - Litt, Dana M.; Stock, Michelle L.; Gibbons, Frederick X.
<x xml:space="preserve">Abstract</x> Objectives Research has indicated that both peers and siblings influence adolescents' alcohol use (e.g., Windle, 2000, Appl. Dev. Sci., 4, 98). The present two studies examined whether social comparison orientation (SCO) moderates the effects of perceived friend and sibling alcohol use on adolescents' alcohol use cognitions and behaviours. Design and methods Two studies examined the role of SCO as a moderator of social influence (perceived friend alcohol use in Study 1 and both perceived friend use and sibling‐reported alcohol use in Study 2) on prototype perceptions and willingness to drink alcohol (Studies 1 and 2) as well as actual alcohol consumption (Study 2) among early adolescents. Results In Study 1, cross‐sectional results indicated that SCO moderated the effect of perceived friend alcohol use on favourable images of drinkers and willingness to drink. Study 2 found that SCO moderated the effects of perceived friend use and sibling use on favourable images of alcohol users, willingness to use alcohol, and change in alcohol use over 3 years such that adolescents who reported engaging in social comparison more often reported greater willingness, more favourable images, and increases in alcohol use when perceived friend use or sibling use was high. Conclusions These studies highlight the importance of SCO as a moderator of susceptibility to the social influences of friends and siblings and may hold important implications for adolescent alcohol use prevention programmes and models of health risk behaviour. <boxed-text content-type="box" id="bjhp12118-blkfxd-0001" position="anchor" orientation="portrait"> Statement of contribution What is already known on this subject? The prevalence of adolescent alcohol use continues to be a public health concern and research has indicated that alcohol use during adolescence is often influenced by the behaviour of friends and siblings. What does this study add? Results add to the literature on the importance of examining person‐level moderators such as of peer and sibling influence on alcohol use cognitions and behaviour according to the prototype/willingness model. Results suggest that considering social comparison orientation as an individual difference variable that may influence adolescents' decisions to engage in alcohol use can potentially increase the efficacy of existing alcohol use programs. </boxed-text>